Response of sunflower cultivars to the density of population in two environments. - Ortegón, Alfredo S. (2006)
Two hybrids of sunflower (Dekalb G-100 G101) and two varieties of free pollination (Rib-77 and Victoria), in three densities of population (31.250, 41.660 62,500 plants/ha) were evaluated. The objective was to determine differences among varieties under climatic conditions of the northern Tamaulipas, Mexico. In 1994 the plantation was established in a cycle considered as “late”; in 1995 a second plantation was established in a cycle considered as “late”. It was used a divided block design in a randomized block distribution with four repetitions. The greater plot corresponded to the cultivars and the minor parcel to the densities of population. Results obtained in the “late” cycle showed a grain yield average of 1.678 kg/ha and in the “early” cycle of 2.170 kg/ha, these results were consistent with the cycles x cultivars interaction. Hybrids and Rib-77 variety were statistically equal in each cycle for grain yield. Hybrids overcame cultivars in oil content. For the densities it was found that for a lower density population produced a higher grain weight, stem diameter, and weight of 100 seeds.